2011
DOI: 10.2478/s11772-010-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical uniform/gradient waveguide sensor structure - characterization

Abstract: The paper presents the characterization of a composite uniform/gradient waveguide sensor structure. The results of theoretical analysis and experimental studies have been presented. The influence of sensor structure parameters on homogenous sensitivity and on surface sensitivity has been analyzed. Gradient layers for composite sensor structures were produced using the ion-exchange method, and the uniform layers, using the sol-gel method. In the experimental studies, involving the produced sensor structures, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…33 Ion-exchanged glasses are routinely used for glass strengthening 34 and gradient waveguide fabrication. 35,36 The ion-exchange method leads to a gradient silver ion concentration and is used for surface modification of the glass. The high silver ion concentration in the close vicinity of the glass surface can play an important role for sensor applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Ion-exchanged glasses are routinely used for glass strengthening 34 and gradient waveguide fabrication. 35,36 The ion-exchange method leads to a gradient silver ion concentration and is used for surface modification of the glass. The high silver ion concentration in the close vicinity of the glass surface can play an important role for sensor applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the structure of silicate glass could be identified on the atomic scale . Ion-exchanged glasses are routinely used for glass strengthening and gradient waveguide fabrication. , The ion-exchange method leads to a gradient silver ion concentration and is used for surface modification of the glass. The high silver ion concentration in the close vicinity of the glass surface can play an important role for sensor applications. , Recently, we demonstrated that low concentrations of biomolecules can be detected on silver ion-exchanged glasses using surface-enhanced Raman scattering (SERS) …”
Section: Introductionmentioning
confidence: 99%
“…/ is the surface sensitivity, n eff is an effective refractive index, n c is a RI of the ambient and w s is a thickness of the sensitive film. High sensitivities are achievable for single modal or bimodal uniform waveguides having high refractive index [11][12][13][14][15][16] . However thicknesses of single or bimodal waveguides which have high refractive index contrast are small, being of the order of wavelength fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Changes of the measurand are transformed into changes of a real part of waveguide modes effective indexes. These changes can be measured using grating couplers 7,8 or planar waveguide interferometers [9][10][11] . The key parameters of PEWS are a homogeneous sensitivity and a surface sensitivity, defined as a derivatives of effective refractive indexes in respect to parameters of a cover: the RI of the ambient and a thickness of the sensitive film.…”
Section: Introductionmentioning
confidence: 99%
“…Optical transfer matrix methods are very useful in the analy− sis of the multilayer optical structures [26][27][28][29][30]. In the theo− retical analysis of a solar cell was used the optical transfer matrix 2×2 method [26,31].…”
Section: Calculation Routinementioning
confidence: 99%